PENGARUH INTELLECTUAL CAPITAL, COST OF CAPITAL, DAN WOMEN ON BOARD TERHADAP NILAI PERUSAHAAN SEKTOR TEKNOLOGI DI INDONESIA - Cahyadi, Andreas; Angela, Aurora (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
The technology industry is a strategic sector that contributes significantly to the global economy. This study aims to analyze the effect of intellectual capital, cost of capital, and female representation on the board of directors on the value of technology companies in Indonesia. This research using technology industry listed on the Indonesia Stock Exchange for the 2019-2023 observation period. The variables used were intellectual capital with VAIC proxies, cost of capital with WACC proxies, and the percentage of women on the board of directors. The hypothesis test uses multiple linear regression. The results of the study indicate that intellectual capital has a significant positive effect on firm value, while cost of capital has a negative but insignificant effect. In addition, female representation on the board of directors significantly increases firm value, reflecting the contribution of gender diversity in strategic decision making. The recommendations of this study are optimal intellectual capital management, reducing the cost of capital, and increasing female representation on the board of directors as a strategy to improve the competitiveness and sustainability of technology companies.